Firm Life Cycle and Investment Inefficiency: Empirical Study in Indonesian Stock Exchange - Amelia Graciosa Guntoro; Gracia; Rita Juliana (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2020)
This paper investigates whether the firm's life cycle stages carry out free cash flow efficiently or not before their investment performance. We utilize cash flow patterns to classify firms into five several life cycles stages. Our data consists of non-financial firms listed in Indonesia Stock Exchange from 2008-2018. We find evidence that Indonesian firms in the introduction, growth, and shakeout stage are underinvesting. This paper also shows that firms in decline stage are overinvested. The characteristic of the mature firm includes that firms with high cash flow will tend to overinvest. However, contrasting with mature firms' common characteristics, our results show that Indonesian firms in maturity stage tend to underinvest. The results also imply that the government should acknowledge the existence of Indonesian firms' investment inefficiency problem. Overall, this paper contributes to the literature by providing empirical evidence on Indonesia's investment inefficiency phenomena. It is suggested that further research may select a different method in calculating growth opportunities and may also study private firms since it tends to have higher financial constraints.